Knowledge sharing behaviour in the public sector: The business process management perspectives - Ahmad, Hartini; Sharom, Normala; Abdullah, Che Sobry (2006)
The purpose of this paper is to demonstrate the preliminary analysis on the knowledge sharing behaviour of the public sectors in terms of individual attitudes, organisational environment, reward system and information and communication technology (ICT) within the system. The paper looks into the perspective of business process management which embedded in a knowledge sharing behaviour. This research-inprogress intends to use both quantitative and qualitative methods (triangulation) because we believe that it will be appropriate to answer the research questions better. In the Phase One, consists of the questionnaire that uses to measure perceptions, beliefs, reactions, and attitudes related to knowledge sharing. The unit of analysis using middle to senior management in the public sector as knowledge is said to be captured more systematically at this level. Phase Two will be carried out after analysis of data from the questionnaire survey is completed. The researcher intends to undertake an in-depth exploration of issues arising from Phase One. Hence a semi-structured interview will be carried out with small group of people. Top management officials will be selected from within the same sample for this exercise. The research design in this study hopefully will answer all the research questions significantly. The preliminary findings will provide a basis for proposing a structured framework for further data collection and analysis.